Traditional postnatal care's (TPC) effects on postpartum mothers' well-being in Malaysia: A concept paper - Patricia Sator; Nurazian Marisen; Walton Wider (WHO Office in Azerbaijan, 2022)
Postpartum care as it was traditionally practised, also known as traditional postnatal care (TPC), is one of the options open to mothers for the purpose of health maintenance and overall wellness, including both physical and mental health. There are many different kinds of TPC, and the approaches are decided upon either by those of a more senior generation, the friends of the mothers, or the mothers themselves. It appears that there has been very little research conducted on the effects of traditional postnatal care on postpartum mothers, and nurses have reported that they have found it challenging to share information about TPC with the local community, particularly in primary health care settings. In this study, an attempt is made to comprehend the existing research regarding the impact that TPC has on the health of postpartum mothers. Because one of the primary responsibilities of the nursing programme is to care for postnatal mothers, introducing or including TPC in the nursing curriculum may improve the nurses' knowledge.